SAMPLING OF MATERIAL FROM AN OBJECT OF PROCESSING ELECTRIC CONDUCTIVITY REDUCED TO ELECTRICAL DISCHARGE MACHINING - Alin NIOAŢĂ; Florin CIOFU (Fiabilitate şi Durabilitate)
The authors have studied some aspects of the mechanism of material removal by electrical discharge machining of a work piece formed by a plate of silicium or germanium placed between plates of steel, aluminum or cooper.